The Proof of the Gibbard-Satterthwaite Theorem Revisited - Lars-Gunnar Svensson (Lund University, School of Economics and Management, Department of Economics, 1999)
This paper provides three short and very simple proofs of the classical Gibbard-Satterthwaite theorem. The theorem is first proved in the case with only two individuals in the economy. The many individual case follows then from an induction argument (over the number of individuals). The proof of the theorem is further simplified when the voting rule is assumed to be neutral.
Keywords: D70; 330; voting; strategy-proofness